Method for preparing catalyst and catalyst prepared by method

By filling alkoxymagnesium particles in paraffin and treating silane chloride compounds, combined with reaction of titanium compounds, a catalyst with small particle size, high spherical shape and stable pore structure was prepared, and the catalyst particle size and The problem of insufficient porosity improves 3D printing performance.

CN119219807APending Publication Date: 2024-12-31CHINA ENERGY GRP NINGXIA COAL IND CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411363256.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The particle size, sphericality and porosity of existing polyolefin catalysts cannot meet the requirements of selective laser sintering (SLS) technology for polyolefin powders, resulting in poor printing performance in 3D printing.

Method used

A method, which involves immersing alkoxymagnesium particles in melted paraffin for pore filling, removing surface paraffin, flattening the surface of the particles with silane chloride compounds, and reacting with the titanium compound at a specific temperature, to prepare A catalyst with small particle size, excellent spherical shape and stable pore structure.

Benefits of technology

It effectively solves the problem of difficult control of catalyst particle size and easy to break. The prepared catalyst has excellent spherical shape and pore structure, which improves the applicability and performance in the preparation of 3D printed polyolefin powders, and meets the requirements of SLS technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005065443750000121
    Figure BDA0005065443750000121
Patent Text Reader

Abstract

The invention provides a method for preparing a catalyst and the catalyst prepared by the method. The method comprises the following steps: immersing alkoxy magnesium particles in molten paraffin, raising the temperature to 70-120 DEG C, and fully stirring to enable pores of the particles to be filled with the paraffin; filtering the mixture of the paraffin and the particles, cooling a filter cake to 0-40 DEG C, and removing the paraffin on the surfaces of the particles; flattening the surfaces of the particles by using a chlorinated silane compound to generate a product mixture; filtering and washing the product mixture to obtain flattened particles; removing paraffin in pores of the flattened particles to obtain porous flattened particles; and adding the porous flattened particles into a titanium compound at a temperature of-20 to 110 DEG C, and reacting to obtain the catalyst. By applying the technical scheme provided by the invention, the problems that the particle size of the catalyst is difficult to control and the catalyst is easy to break in the prior art can be solved, and the prepared small-particle-size catalyst has excellent sphericity and can retain the pore structure of original particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of polyolefin catalysts, and in particular to a method for preparing a catalyst and a catalyst prepared thereby. Background Art

[0002] As the world's leading synthetic resin, polyolefins are deeply rooted in every corner of modern society, including industrial production, agriculture, construction industry, medical and health care, and daily consumer goods, with their excellent physical and mechanical properties, outstanding thermal stability and processing adaptability, wide range of crystallinity adjustment, excellent chemical corrosion resistance, economical cost, and environmentally friendly recyclable properties. As the core driving force of the polyolefin industry, the continuous innovation and progress of catalyst technology has directly promoted the development and application of new polyolefin materials.

[0003] In recent years, with the rapid development of additive manufacturing technology, especially the maturity of selective laser sintering (SLS) technology, the application scope of polyolefins has been further expanded. SLS technology places strict requirements on the particle size distribution and fluidity of polyolefin powders to ensure uniformity and stability during the printing process. The ideal polyolefin powder should have a particle size of 20 to 100 microns, or even smaller, and have good fluidity.

[0004] Currently, the production of polyolefin powder suitable for 3D printing mainly relies on cryogenic ball milling and in-situ polymerization. Among them, the in-situ polymerization method shows obvious advantages in particle size control and fluidity, surpassing the traditional cryogenic ball milling process. However, the particle size range of commonly used polyolefin catalysts is not suitable for directly preparing the polyolefin powder required for SLS technology. Therefore, it is urgent to develop new polyolefin catalysts with smaller particle sizes to meet the specific requirements of SLS technology for polyolefin powder.

[0005] The present invention is aimed at this demand and is committed to developing a method for preparing a polyolefin catalyst that can produce a smaller particle size, better sphericity, and more stable pore structure, so as to promote the application of polyolefin materials in the field of 3D printing and improve their printing performance. Summary of the invention

[0006] The main purpose of the present invention is to provide a method for preparing a catalyst and a catalyst prepared thereby, so as to solve the problem that the particle size, sphericity and porosity of the catalyst prepared by the method in the prior art cannot meet the requirements of the SLS technology.

[0007] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided a method for preparing a catalyst, comprising the following steps: S1, immersing alkoxy magnesium particles in melted paraffin, heating to a temperature in the range of 70 to 120°C, and stirring sufficiently so that the pores of the particles are filled with paraffin; S2, filtering the mixture of paraffin and particles, cooling the filter cake to a temperature in the range of 0 to 40°C, and removing the paraffin on the surface of the particles; S3, using a chlorosilane compound to smooth the surface of the particles to generate a product mixture; S4, filtering and washing the product mixture to obtain smoothed particles; S5, removing the paraffin in the pores of the smoothed particles to obtain porous smoothed particles; and S6, adding the porous smoothed particles to a titanium compound at a temperature of -20 to 110°C to react to obtain a catalyst.

[0008] Further, in the above method, the molar ratio of total chlorine atoms in the chlorinated silane compound to total magnesium atoms in the alkoxymagnesium particles is in the range of 1.75:1 to 1.985:1.

[0009] Further, in the above method, the alkoxy magnesium particles include dimethoxy magnesium, diethoxy magnesium, dipropoxy magnesium, dibutoxy magnesium, dioctyloxy magnesium or any combination thereof.

[0010] Further, in the above method, the particle size of the alkoxy magnesium particles is in the range of 5 μm to 10 μm.

[0011] Furthermore, in the above method, the porosity of the alkoxy magnesium particles is 0.1 cm 3 / g to 1cm 3 / g range.

[0012] Furthermore, in the above method, step S2 further includes removing paraffin on the surface of the particles using a first solvent, and the first solvent is an alkane solvent.

[0013] Furthermore, in the above method, the first solvent is selected from n-hexane, cyclohexane, n-octane, isooctane, xylene, toluene, ethane, propane and any combination thereof.

[0014] Furthermore, in the above method, step S3 further comprises dispersing the mixture in a second solvent, adding a chlorinated silane compound, so that the chlorinated silane compound reacts with the alkoxymagnesium on the surface of the particles, wherein the second solvent is a poor solvent for paraffin.

[0015] Furthermore, in the above method, the second solvent is selected from water, methanol, ethanol, glycerol and any combination thereof.

[0016] Furthermore, in the above method, the chlorinated silane compound is selected from SiC1 4 、Si(OCH3 )Cl 3 、Si(OCH 3 ) 2 Cl 2 、Si(OC 2 H 5 )Cl 3 、Si(OC 2 H 5 ) 2 Cl 2 、Si(OC 2 H 5 ) 3 Cl、Si(OC 4 H 9 )Cl 3 、Si(OC 4 H 9 ) 2 Cl 2 、Si(OC 4 H 9 ) 3 Cl and any combination thereof.

[0017] Furthermore, in the above method, the titanium compound is selected from TiC1 4 、TiC1 3 、Ti(OCH 3 )Cl 3 、Ti(OCH 3 ) 2 Cl 2 、Ti(OCH 3 ) 3 Cl、Ti(OC 2 H 5 )Cl 3 、Ti(OC 2 H 5 ) 2 Cl 2 、Ti(OC 2 H 5 ) 3 Cl、Ti(OC 4 H 9 )Cl 3 、Ti(OC 4 H 9 ) 2 Cl 2 、Ti(OC 4 H 9 ) 3 Cl and any combination thereof.

[0018] Further, in the above method, a molar ratio of the porous planarizing particles to the titanium compound is in the range of 1:20 to 1:100.

[0019] According to another aspect of the present invention, a catalyst prepared according to the method of the present invention is provided.

[0020] The application of the technical solution of the present invention can effectively solve the problems in the prior art that the catalyst particle size is difficult to control and easy to break. The prepared small-particle catalyst not only has excellent sphericity, but also can retain the pore structure of the original particles, thereby improving the applicability and performance of the catalyst in the preparation of 3D printed polyolefin powders. DETAILED DESCRIPTION

[0021] It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments. The following embodiments are merely exemplary and do not constitute a limitation on the scope of protection of the present invention.

[0022] As described in the background art, the particle size, sphericity and pore structure of the polyolefin powder produced by the methods in the prior art cannot meet the requirements of the SLS technology for polyolefin powder. In view of the problems in the prior art, a typical embodiment of the present invention provides a method for preparing a catalyst, which comprises the following steps: S1, immersing alkoxy magnesium particles in melted paraffin, heating to a temperature in the range of 70 to 120°C, and stirring sufficiently so that the pores of the particles are filled with paraffin; S2, filtering the mixture of paraffin and particles, cooling the filter cake to a temperature in the range of 0 to 40°C, and removing the paraffin on the surface of the particles; S3, using a chlorosilane compound to smooth the surface of the particles to generate a product mixture; S4, filtering and washing the product mixture to obtain smoothed particles; S5, removing the paraffin in the pores of the smoothed particles to obtain porous smoothed particles; and S6, adding the porous smoothed particles to a titanium compound at a temperature of -20 to 110°C to react to obtain a catalyst.

[0023] Different from the method for preparing polyolefin in the prior art, in the method for preparing the catalyst of the present invention, alkoxy magnesium particles (such as ethoxy magnesium) of a specific particle size range are first immersed in melted paraffin, and the temperature is controlled within the range of 70°C to 120°C, and the mixture is fully stirred to ensure that the liquid paraffin can be evenly diffused into the pores inside the particles, thereby filling the pores inside the particles. The purpose of this step is to utilize the filling effect of the paraffin to protect the internal pore structure of the particles from being destroyed by subsequent chemical reactions, and at the same time provide a stable "template" for subsequent steps.

[0024] The mixture of paraffin wax and alkoxy magnesium particles is then filtered to separate the filter cake filled with paraffin wax, and the filter cake temperature is lowered to a range of 0°C to 40°C, and a suitable alkane solvent (such as hexane, heptane, etc.) is used for rapid washing to remove the residual paraffin wax on the particle surface. This step is to clean the particle surface to avoid the interference of paraffin wax in subsequent reactions, while maintaining the filling state of the internal pores.

[0025] After removing the surface paraffin, use chlorinated silane compounds (such as silicon tetrachloride SiCl 4 ) reacts with excess alkoxymagnesium particles to flatten the surface of the particles to form a product mixture. The reaction of silicon tetrachloride with alkoxymagnesium can produce magnesium chloride (MgCl 2 ) and silanol esters (Si(OEt) 4 ), this chemical reaction process helps to change the surface properties of the particles, providing more stable and uniform active sites for subsequent titanium compound reactions.

[0026] The resulting product mixture is then filtered and washed with anhydrous ethanol to remove the generated magnesium chloride byproduct, thereby obtaining the alkoxy magnesium particles after planarization (i.e., planarized particles). In this step, ethanol is used to effectively wash away the magnesium chloride while avoiding damage to the structure of the alkoxy magnesium particles.

[0027] The flattened particles obtained in the above step are added to an alkane solvent, such as hexane, and the temperature is raised to a range of 70°C to 120°C, and stirred sufficiently to elute the paraffin in the pores inside the particles, thereby obtaining porous flattened particles with complete internal pore structure and flat surface. This step ensures the integrity of the pores inside the particles, providing the necessary conditions for the subsequent preparation of the catalyst.

[0028] Finally, the obtained porous planarized particles are added to a titanium compound (such as titanium tetrachloride TiCl 4 ), and add an internal electron donor (such as diisobutyl phthalate) during the reaction, and by precisely controlling the reaction conditions (such as temperature, time, and the ratio of the titanium compound to the internal electron donor), filtering, washing, drying, and other steps are performed after the reaction to obtain the final small-particle catalyst. In this step, the formation of the catalyst active center and the control of the particle size can be achieved through the reaction of the titanium compound and the internal electron donor, while ensuring that the catalyst has good sphericity and flow properties, which is suitable for the application of selective laser sintering in 3D printing technology.

[0029] Through the above steps, the present invention can effectively solve the problems in the prior art that the catalyst particle size is difficult to control and easy to break. The prepared small-particle catalyst not only has excellent sphericity, but also can retain the pore structure of the original particles, thereby improving the applicability and performance of the catalyst in the preparation of 3D printed polyolefin powder.

[0030] In some embodiments of the present invention, in step S1, the temperature may be raised to 70°C to 120°C, 80°C to 110°C, 90°C to 100°C, 70°C to 110°C, 70°C to 100°C, 70°C to 90°C, 70°C to 80°C, 80°C to 120°C, 90°C to 120°C, 100°C to 120°C, or 110°C to 120°C. In step S2, the filter cake may be cooled to a temperature in the range of 0°C to 40°C, 5°C to 35°C, 10°C to 30°C, 15°C to 25°C, 0°C to 30°C, 0°C to 20°C, 0°C to 10°C, 10°C to 40°C, 20°C to 40°C, or 30°C to 40°C. In step S6, the reaction temperature of the porous planarized particles and the titanium compound may be in the range of -20°C to 110°C, -10°C to 100°C, 0°C to 90°C, 10°C to 80°C, 20°C to 70°C, 30°C to 60°C, 40°C to 50°C, -20°C to 100°C, -20°C to 90°C, -20°C to 80°C, -20°C to 70°C, -20°C to 60°C, -20°C to 50°C, -10°C to 110°C, 0°C to 110°C, 10°C to 110°C, 20°C to 110°C, 20°C to 110°C, 40°C to 110°C, 50°C to 110°C, 60°C to 110°C, 70°C to 110°C, 80°C to 110°C or 90°C to 110°C.

[0031] In some embodiments of the present invention, the alkoxy magnesium particles used include but are not limited to dimethoxy magnesium (Mg(OMe) 2 )、diethoxymagnesium (Mg(OEt) 2 ), dipropoxymagnesium (Mg(OPr) 2 ), dibutoxymagnesium (Mg(OBu) 2 ), dioctyl magnesium (Mg(OC 8 H 17 ) 2 ) or any combination thereof. These alkoxy magnesium particles, due to their unique chemical properties and structure, can serve as effective catalyst precursors and play an important role in the polyolefin preparation process. Specifically, they can be converted into active polyolefin catalysts under certain conditions, for example, by reacting with titanium tetrachloride (TiCl 4 ) or other transition metal halides to generate catalyst particles containing metal active centers, which can efficiently catalyze the polymerization of olefins to obtain high molecular weight polyolefins.

[0032] In the preparation method of the present invention, by selecting different types of alkoxy magnesium particles, the properties of the catalyst, such as particle size, sphericity and pore structure, can be adjusted according to the performance requirements of the target polyolefin powder. For example, diethoxy magnesium is a common raw material for preparing polypropylene catalysts due to its high activity and good thermal stability; while dipropoxy magnesium and dibutoxy magnesium may be more suitable for preparing polypropylene catalysts with specific crystallinity and molecular weight distribution.

[0033] The present invention adopts chemical etching combined with pretreatment of alkoxy magnesium particles, which can not only prepare granular catalysts with smaller particle size, but also these catalysts have a high degree of sphericity and a stable pore structure, greatly improving the flow properties of polyolefin powder, making it more suitable for the selective laser sintering (SLS) process in 3D printing technology. This method avoids the morphological destruction that may occur in the process of preparing catalysts by traditional high shear methods, thereby retaining the original high sphericity characteristics of the catalyst, while achieving effective management of particle size through precise chemical control.

[0034] In a further embodiment, the particle size of the alkoxy magnesium particles used in step S1 of the present invention is in the range of 5 μm to 10 μm. In a preferred embodiment, the particle size of the alkoxy magnesium particles may be in the following ranges: 5 μm to 10 μm, 6 μm to 9 μm, 7 μm to 8 μm, 5 μm to 9 μm, 5 μm to 8 μm, 5 μm to 7 μm, 5 μm to 6 μm, 6 μm to 10 μm, 7 μm to 10 μm, 8 μm to 10 μm or 9 μm to 10 μm.

[0035] In the method for preparing the catalyst of the present invention, the alkoxy magnesium particles need to react with silicon tetrachloride, and the particles with a particle size between 5 μm and 10 μm can ensure that the reaction is carried out under sufficient contact area, while avoiding the problem that too small particles are quickly consumed in the reaction, or too large particles cause insufficient reaction. Alkoxy magnesium particles with a particle size of less than 5 μm may be over-etched in subsequent reactions, resulting in a reduction in the active sites of the catalyst, thereby affecting the efficiency and selectivity of the catalyst. Particles with a particle size of more than 10 μm may be difficult to disperse evenly during the preparation process, thereby affecting the uniformity of the catalyst and the particle size control of the final product. In order to meet the particle size requirements of 3D printing selective laser sintering (SLS) technology for polyolefin powders, alkoxy magnesium particles with a particle size of 5 μm to 10 μm are used as catalysts. In the subsequent olefin polymerization process, by controlling the reaction conditions, such as temperature, pressure, reaction time, and the type and amount of the internal electron donor, a polyolefin powder with a particle size range that meets the requirements is prepared, while ensuring the fluidity and molding properties of the powder. Within this particle size range, the preparation and subsequent processing of alkoxy magnesium particles are relatively easy to control, which is conducive to the standardization and optimization of the catalyst preparation process, thereby improving the repeatability of the experiment and the quality consistency of the catalyst product.

[0036] In a further embodiment, the porosity of the alkoxy magnesium particles used in step S1 of the present invention is 0.1 cm 3 / g to 1cm 3 / g, more preferably 0.3 cm 3 / g to 0.8cm 3 In various embodiments, the porosity of the alkoxy magnesium particles may be in the following ranges: 0.1 cm 3 / g to 1cm 3 / g, 0.2cm 3 / g to 0.9cm 3 / g, 0.3cm 3 / g to 0.8cm 3 / g, 0.4cm 3 / g to 0.7cm 3 / g, 0.5cm 3 / g to 0.6cm 3 / g, 0.1cm 3 / g to 0.9cm 3 / g, 0.1cm 3 / g to 0.8cm 3 / g, 0.1cm 3 / g to 0.7cm 3 / g, 0.1cm 3 / g to 0.6cm 3 / g, 0.1cm 3 / g to 0.5cm 3 / g, 0.1cm 3 / g to 0.4cm 3 / g, 0.1cm 3 / g to 0.3cm 3 / g, 0.2cm 3 / g to 1cm 3 / g, 0.3cm 3 / g to 1cm 3 / g, 0.4cm 3 / g to 1cm 3 / g, 0.5cm 3 / g to 1cm 3 / g, 0.6cm 3 / g to 1cm 3 / g, 0.7cm 3 / g to 1cm 3 / g or 0.8cm 3 / g to 1cm 3 / g. The porosity within the above range of the present invention is crucial to the distribution of active centers and reaction efficiency of the catalyst. If the porosity is too low, the distribution of active centers may be too dense, resulting in limited diffusion inside the catalyst during the reaction, affecting the uniformity and efficiency of the polymerization reaction; if the porosity is too high, although it is conducive to the diffusion of reactants and products, it may lead to a decrease in the stability of the catalyst structure, which is easy to break or deform during the reaction, affecting the particle size control and sphericity of the catalyst.

[0037] In order to achieve this preferred porosity range, the present invention adopts a specific pretreatment method. First, high-viscosity liquid paraffin is selected as a pore filler, which can penetrate into the microporous structure of the alkoxy magnesium particles to form a protective film to prevent the pore structure from being destroyed in subsequent chemical reactions. The viscosity of the liquid paraffin should be controlled within an appropriate range. Too high or too low is not conducive to its uniform distribution in the pores. Secondly, after the alkoxy magnesium particles are dispersed in the liquid paraffin, they need to be fully stirred at a specific temperature to promote the penetration of the liquid paraffin. This temperature is usually between 80°C and 120°C, and the specific temperature needs to be adjusted according to the specific properties of the alkoxy magnesium particles. During the stirring process, it is also necessary to control the stirring speed to avoid particle breakage due to excessive stirring.

[0038] In the method of the present invention, accurate chemical equivalent design is the key to optimizing the catalyst porosity. By carefully controlling the molar ratio between silicon tetrachloride and alkoxymagnesium particles, the pore structure of the catalyst can be precisely adjusted while maintaining high sphericity to meet the strict requirements of 3D printing, especially selective laser sintering technology, on the fluidity and particle size of polyolefin powders.

[0039] During the chemical etching process, the reaction between silicon tetrachloride and alkoxymagnesium particles is the core step in the preparation of the catalyst. Silicon tetrachloride can not only react with alkoxymagnesium to generate magnesium chloride, but also remove the alkoxymagnesium on the surface by chemical etching, thereby regulating the surface sphericity and porosity of the alkoxymagnesium particles. Although excess silicon tetrachloride helps the reaction to proceed completely, too high an excess ratio will lead to an excessive etching reaction, destroying the original pore structure of the alkoxymagnesium, thereby reducing the porosity of the catalyst and affecting its catalytic activity and selectivity.

[0040] Therefore, the present invention particularly emphasizes controlling the molar ratio of the total chlorine atoms in the chlorosilane compound to the total magnesium atoms in the alkoxymagnesium particles, preferably in the range of 1.751:1 to 1.985:1. Within this molar ratio range, silicon tetrachloride can fully react and effectively etch the alkoxymagnesium particles without excessively destroying their pore structure. By accurately controlling this chemical equivalent ratio, a polyolefin catalyst with high sphericity, suitable particle size and optimized porosity can be prepared.

[0041] In addition, in order to further improve the performance of the catalyst, the present invention also considers the optimization of reaction conditions, including precise control of parameters such as reaction temperature, reaction time and stirring speed. Through the coordinated regulation of these parameters, the stability of the catalyst can be further enhanced and its catalytic efficiency can be improved, thereby more effectively controlling the particle size distribution of the polyolefin powder during the in-situ polymerization of polyolefins, ensuring its fluidity and printing performance.

[0042] Through the above method, the present invention can not only prepare small particle catalysts with a particle size of less than 5 μm, but also ensure that the catalyst has a high sphericity and a stable pore structure, thereby improving the activity and selectivity of the catalyst in olefin polymerization reactions. The final polyolefin powder has better fluidity and particle size distribution, and is very suitable for the selective laser sintering (SLS) process in 3D printing technology.

[0043] In step S2 of the present invention, the process of removing paraffin on the particle surface is crucial, which directly affects the quality and performance of the subsequent catalyst preparation. Using the first solvent for washing can not only effectively remove the paraffin remaining on the particle surface, but also ensure that the surface of the ethoxy magnesium particles is clean, creating favorable conditions for subsequent reactions.

[0044] The first solvent is preferably an alkane solvent, which is based on the fact that alkane solvents have good mutual solubility and low polarity with paraffin, can efficiently dissolve and remove paraffin on the surface, and will not have unnecessary chemical reactions with ethoxy magnesium particles, maintaining their activity and structural integrity. In addition, alkane solvents are easy to obtain in both industrial production and laboratory preparation, and the cost is relatively low, which is conducive to the large-scale preparation of catalysts.

[0045] In a further embodiment, the first solvent can be n-hexane, cyclohexane, n-octane, isooctane, xylene, toluene, ethane, propane or any combination thereof. The selection basis of these solvents is their boiling point, solubility and safety. For example, n-hexane and cyclohexane are commonly used for removing surface paraffin due to their lower boiling point and good solubility; while xylene and toluene are more effective in treating some difficult-to-remove paraffins due to their higher boiling point and stronger solubility. Ethane and propane are suitable for rapid washing operations due to their lower boiling points, but attention should be paid to their gas-liquid conversion control at low temperatures.

[0046] In actual operation, the appropriate solvent or solvent combination can be selected according to specific needs and experimental conditions. For example, in order to improve the washing efficiency, a solvent with a lower boiling point (such as ethane or propane) can be used to quickly remove most of the paraffin on the surface, and then a solvent with a higher boiling point (such as n-hexane or cyclohexane) can be used for deep washing to ensure that the residual paraffin is reduced to a minimum. Such an operation process can not only effectively improve the purity of the catalyst, but also optimize production efficiency, reduce energy consumption, and achieve dual control of cost and quality.

[0047] When washing with solvents, it is also necessary to control the amount of solvent used and the washing time to avoid excessive washing that may cause changes in the physical properties (such as porosity) of the ethoxy magnesium particles, thereby affecting the performance of the final catalyst. In addition, since some solvents are toxic or flammable, safety regulations should be strictly followed during operation, and appropriate protective measures should be used to ensure production safety.

[0048] In step S3 of the present invention, the mixture is further dispersed in a second solvent, and a silane chloride compound is added to react with the magnesium alkoxide on the surface of the particles, wherein the second solvent is a poor solvent for paraffin. The second solvent is selected from water, methanol, ethanol, glycerol and any combination thereof.

[0049] In step S3 of the present invention, in order to further optimize the preparation process of the catalyst and enhance its performance, the present invention discloses an improved preparation step:

[0050] The treated alkoxymagnesium particles are dispersed in a second solvent. The second solvent should be a poor solvent for paraffin wax, which means that paraffin wax will not dissolve in it, thereby helping to protect the internal structure of the particles from being damaged, while ensuring that the alkoxymagnesium part of the particle surface can be exposed and react with the subsequently added chlorinated silane compound. The choice of the second solvent has an important impact on the performance of the final catalyst. It should be able to effectively dissolve the chlorinated silane compound and provide a stable environment during the reaction.

[0051] Add chlorinated silane compounds. The role of chlorinated silane compounds in this step is to react with the alkoxymagnesium on the surface of the alkoxymagnesium particles to generate intermediates with specific chemical properties, thereby changing or optimizing the properties of the particle surface and laying the foundation for the subsequent formation of catalyst active centers. The selection of chlorinated silane compounds should not only consider their reactivity with alkoxymagnesium, but also their effect on the final catalyst performance, such as improving the activity, selectivity or stability of the catalyst.

[0052] The selection range of the second solvent includes but is not limited to water, methanol, ethanol, glycerol and various combinations thereof. The selection of different solvents will affect the solubility and reaction rate of the chlorosilane compounds, and thus affect the final performance of the catalyst. For example, when glycerol is used as the second solvent, due to its higher viscosity and polarity, it can slow down the diffusion rate of the chlorosilane compounds, which helps to more accurately control the reaction process, thereby obtaining catalyst particles with narrower particle size distribution and higher sphericity. When water is used as the second solvent, the reaction rate may be faster, but special attention should be paid to the removal of water to avoid adverse effects on subsequent catalyst activity.

[0053] Preferably, the second solvent is ethanol or glycerol. Ethanol has good solubility and low viscosity, which can ensure that the chlorinated silane compounds can quickly and evenly contact the surface of the alkoxymagnesium particles, and the reaction rate is moderate and easy to control; glycerol can provide a slower reaction environment due to its higher viscosity, which is conducive to the uniformity of the particle surface reaction. At the same time, the polarity of glycerol helps to protect the internal structure of the particles, reduce the reaction of the internal pores with the chlorinated silane compounds, thereby retaining more pore structures, and has a positive effect on the porosity and specific surface area of ​​the catalyst.

[0054] In the embodiment, the treated ethoxy magnesium particles are dispersed in glycerol, and then silicon tetrachloride is added to react. Glycerol, as a poor solvent for paraffin, can effectively prevent paraffin from dissolving during the reaction, while ensuring that silicon tetrachloride is fully in contact with the surface of the ethoxy magnesium particles, and the intermediate product generated by the reaction has good chemical stability and active center formation potential. After the reaction is completed, the mixture is separated by filtration, and the filter cake is washed with anhydrous ethanol to remove the generated magnesium chloride; then, the filter cake is added to hexane to further elute the paraffin in the pores inside the particles to ensure the cleanliness and activity of the pores inside the catalyst.

[0055] This improved step S3 can more effectively control the particle size and shape of the catalyst particles while maintaining the integrity of its internal pore structure, thereby improving the application effect of the catalyst in the preparation of polyolefin powder for 3D printing, and obtaining polyolefin powder with smaller particle size and better flowability, meeting the strict requirements of selective laser sintering (SLS) technology for materials.

[0056] In a preferred embodiment of the present invention, the chlorinated silane compound is selected from SiCl 4 、Si(OCH 3 )Cl 3 、Si(OCH 3 ) 2 Cl 2 、Si(OC 2 H 5 )Cl 3 、Si(OC 2 H 5 ) 2 Cl 2 、Si(OC 2 H 5 ) 3 Cl、Si(OC 4 H 9 )Cl 3 、Si(OC 4 H 9 ) 2 Cl 2 、Si(OC 4 H 9 ) 3 C and any combination thereof. In addition, in some other preferred embodiments, the titanium compound is selected from TiC1 4 、TiC1 3 、Ti(OCH 3 )Cl 3 、Ti(OCH 3 ) 2 Cl 2 、Ti(OCH 3 ) 3 Cl、Ti(OC 2 H 5 )Cl 3 、Ti(OC 2 H 5 ) 2 Cl 2 、Ti(OC 2 H 5 ) 3 Cl、Ti(OC 4 H 9 )Cl 3 、Ti(OC 4 H 9 ) 2 Cl 2 、Ti(OC 4 H 9 ) 3 Cl and any combination thereof.

[0057] In the catalyst preparation process of the present invention, the molar ratio of the porous flattened particles (taking ethoxymagnesium particles as an example) to the titanium compound (such as titanium tetrachloride) is a key parameter, which directly affects the active center density, particle size distribution and performance of the final polyolefin product of the catalyst. Specifically, the preferred molar ratio of the present invention is in the range of 1:20 to 1:100, more preferably 1:40 to 1:80.

[0058] When the molar ratio of the porous planarized particles to the titanium compound is lower than 1:100, the amount of the titanium compound is relatively excessive, which may cause the titanium active centers on the surface of the catalyst particles to be too dense, thereby affecting the fluidity of the catalyst and even causing agglomeration during the polymerization process, which is not conducive to obtaining polyolefin powder with uniform particle size and good fluidity. On the other hand, excessive titanium compounds may cause unnecessary side reactions, resulting in reduced catalyst activity.

[0059] On the contrary, when the molar ratio of the porous planarized particles to the titanium compound is higher than 1:20, the amount of the titanium compound is relatively insufficient, and the active center density of the catalyst may be too low, which will slow down the polymerization rate of the polyolefin and affect the production efficiency. In addition, the insufficient amount of the titanium compound may also affect the performance of the catalyst, such as catalytic efficiency and selectivity, thereby affecting the quality and performance of the final polyolefin product.

[0060] In the molar ratio range of 1:20 to 1:100, especially in the more preferred range of 1:40 to 1:80, it is possible to ensure full utilization of the internal pore structure of the catalyst, while maintaining a suitable density of titanium active centers, which is conducive to uniform dispersion of the catalyst and control of particle size, thereby improving the comprehensive performance of polyolefin products. In addition, by precisely controlling this molar ratio, the activity of the catalyst can also be adjusted to achieve the best effect in the preparation of polyolefin powder for 3D printing.

[0061] In summary, the present invention not only solves the problem of particle size control in the preparation process of small particle catalysts by optimizing the molar ratio of porous flattened particles to titanium compounds, but also ensures high activity and good flow properties of the catalyst, providing a technical basis for preparing high-quality polyolefin powder suitable for SLS technology.

[0062] According to another typical embodiment of the present invention, a catalyst prepared according to the above method of the present invention is provided.

[0063] Example

[0064] Example 1

[0065] First, 100 g of spherical diethoxy magnesium particles were evenly dispersed in 500 ml of molten paraffin and stirred at 100°C to ensure that the paraffin could fully penetrate into the pores inside the diethoxy magnesium particles. The spherical diethoxy magnesium particles used had a particle size of 10 μm and a porosity of 0.5 cm 3 / g. Subsequently, the paraffin is removed by filtration, the resulting filter cake is cooled at 40°C, and the alkane solvent n-hexane is used for rapid washing to thoroughly remove the paraffin residue on the surface of the particles. The diethoxymagnesium particles treated in this step are further dispersed in a glycerol medium, and then reacted with 65g of silicon tetrachloride under controlled conditions. After the reaction is completed, the mixture is filtered, and then the filter cake is immersed in anhydrous ethanol and stirred to wash away the magnesium chloride generated by the reaction. After filtration, the filter cake is transferred to a n-hexane solvent again, and is fully stirred under heating to effectively elute the paraffin from the internal pores of the diethoxymagnesium particles, and finally filtered and dried to obtain pure diethoxymagnesium catalyst particles. In this embodiment, the molar ratio of chlorine in silicon tetrachloride to magnesium in diethoxymagnesium particles is 1.751:1.

[0066] Next, at a low temperature of -20°C, 6 grams of the above-treated and dried diethoxymagnesium particles were added to 200 ml of titanium tetrachloride solution, and the temperature was gradually raised to 110°C to start the catalyst modification reaction. At this stage, 2 grams of diisobutyl phthalate were added as an internal electron donor to promote the reaction, and the reaction was maintained for 2 hours. Subsequently, the solvent in the reaction solution was filtered out, 200 ml of titanium tetrachloride was added again, the reaction temperature was maintained at 110°C, and the reaction was continued for 2 hours to fully ensure the modification of the catalyst. The total molar ratio of diethoxymagnesium to titanium tetrachloride in the above reaction was 1:70. After the reaction, the product was thoroughly washed and dried, and 6.99 grams of fine small particle size catalyst was finally obtained.

[0067] Example 2

[0068] First, 100 g of spherical dimethoxy magnesium particles were evenly dispersed in 500 ml of molten paraffin and stirred at 70°C to ensure that the paraffin could fully penetrate into the pores inside the dimethoxy magnesium particles. The spherical dimethoxy magnesium particles used had a particle size of 5 μm and a porosity of 0.1 cm 3 / g. Subsequently, the paraffin is removed by filtration, the resulting filter cake is cooled at 0°C, and the alkane solvent cyclohexane is used for rapid washing to thoroughly remove the paraffin residue on the surface of the particles. The dimethoxymagnesium particles treated in this step are further dispersed in an aqueous medium, and then reacted with 97.6g of silicon tetrachloride under controlled conditions. After the reaction is completed, the mixture is filtered, and then the filter cake is immersed in anhydrous ethanol and stirred to wash away the magnesium chloride generated by the reaction. After filtration, the filter cake is transferred to a cyclohexane solvent again, and is fully stirred under heating to effectively elute the paraffin from the internal pores of the dimethoxymagnesium particles. Finally, after filtration and drying, pure dimethoxymagnesium catalyst particles are obtained. In this embodiment, the molar ratio of chlorine in silicon tetrachloride to magnesium in dimethoxymagnesium particles is 1.985:1.

[0069] Next, at a low temperature of -20°C, 6 grams of the treated and dried dimethoxymagnesium particles were added to 250 ml of titanium tetrachloride solution, and the temperature was gradually raised to 110°C to start the catalyst modification reaction. At this stage, 2 grams of diisobutyl phthalate were added as an internal electron donor to promote the reaction, and the reaction was maintained for 2 hours. Subsequently, the solvent in the reaction solution was filtered out, 250 ml of titanium tetrachloride was added again, the reaction temperature was maintained at 110°C, and the reaction was continued for 2 hours to fully ensure the modification of the catalyst. The total molar ratio of dimethoxymagnesium to titanium tetrachloride in the above reaction was 1:75. After the reaction was completed, the product was thoroughly washed and dried, and 9.26 grams of fine small particle size catalyst was finally obtained.

[0070] Example 3

[0071] First, 100 g of spherical dipropoxy magnesium particles were evenly dispersed in 500 ml of molten paraffin and stirred at 90°C to ensure that the paraffin could fully penetrate into the pores inside the dipropoxy magnesium particles. The spherical dipropoxy magnesium particles used had a particle size of 8 μm and a porosity of 1 cm 3 / g. Subsequently, the paraffin is removed by filtration, the resulting filter cake is cooled at 40°C, and the alkane solvent n-octane is used for rapid washing to thoroughly remove the paraffin residue on the surface of the particles. The dipropoxymagnesium particles treated in this step are further dispersed in an ethanol medium, and then reacted with 56.5g of silicon tetrachloride under controlled conditions. After the reaction is completed, the mixture is filtered, and then the filter cake is immersed in anhydrous ethanol and stirred to wash away the magnesium chloride generated by the reaction. After filtration, the filter cake is transferred to the n-octane solvent again, and is fully stirred under heating to effectively elute the paraffin from the internal pores of the dipropoxymagnesium particles. Finally, after filtration and drying, pure dipropoxymagnesium catalyst particles are obtained. In this embodiment, the molar ratio of chlorine in silicon tetrachloride to magnesium in the dipropoxymagnesium particles is 1.896:1.

[0072] Next, under a low temperature of -20°C, 6 grams of the above-treated and dried dipropoxymagnesium particles were added to 150 ml of titanium tetrachloride solution, and the temperature was gradually raised to 110°C to start the catalyst modification reaction. At this stage, 2 grams of diisobutyl phthalate were added as an internal electron donor to promote the reaction, and the reaction was maintained for 2 hours. Subsequently, the solvent in the reaction solution was filtered out, 150 ml of titanium tetrachloride was added again, the reaction temperature was maintained at 110°C, and the reaction was continued for 2 hours to fully ensure the modification of the catalyst. The total molar ratio of dipropoxymagnesium to titanium tetrachloride in the above reaction was 1:65. After the reaction was completed, the product was thoroughly washed and dried, and 5.61 grams of fine small particle size catalyst was finally obtained.

[0073] Example 4

[0074] First, 100 g of spherical dibutoxy magnesium particles were evenly dispersed in 500 ml of molten paraffin and stirred at 120°C to ensure that the paraffin could fully penetrate into the pores inside the dibutoxy magnesium particles. The spherical dibutoxy magnesium particles used had a particle size of 7 μm and a porosity of 0.8 cm 3 / g. Subsequently, the paraffin is removed by filtration, the resulting filter cake is cooled at 20°C, and the alkane solvent xylene is used for rapid washing to thoroughly remove the paraffin residue on the surface of the particles. The dibutoxymagnesium particles treated in this step are further dispersed in a methanol medium, and then reacted with 47.6g of silicon tetrachloride under controlled conditions. After the reaction is completed, the mixture is filtered, and then the filter cake is immersed in anhydrous ethanol and stirred to wash away the magnesium chloride generated by the reaction. After filtration, the filter cake is transferred to a xylene solvent again, and is fully stirred under heating to effectively elute the paraffin from the internal pores of the dibutoxymagnesium particles. Finally, after filtration and drying, pure dibutoxymagnesium catalyst particles are obtained. In this embodiment, the molar ratio of chlorine in silicon tetrachloride to magnesium in the dibutoxymagnesium particles is 1.912:1.

[0075] Next, at a low temperature of -20°C, 6 grams of the above-treated and dried dibutoxymagnesium particles were added to 140 ml of titanium tetrachloride solution, and the temperature was gradually raised to 110°C to start the catalyst modification reaction. At this stage, 2 grams of diisobutyl phthalate were added as an internal electron donor to promote the reaction, and the reaction was maintained for 2 hours. Subsequently, the solvent in the reaction solution was filtered out, 140 ml of titanium tetrachloride was added again, the reaction temperature was maintained at 110°C, and the reaction was continued for 2 hours to fully ensure the modification of the catalyst. The total molar ratio of dibutoxymagnesium to titanium tetrachloride in the above reaction was 1:72. After the reaction, the product was thoroughly washed and dried, and 4.69 grams of fine small particle size catalyst was finally obtained.

[0076] Example 5

[0077] First, 100 g of spherical dioctyl magnesium particles were evenly dispersed in 500 ml of molten paraffin and stirred at 100°C to ensure that the paraffin could fully penetrate into the pores inside the dioctyl magnesium particles. The spherical dioctyl magnesium particles used had a particle size of 6 μm and a porosity of 0.6 cm 3 / g. Subsequently, the paraffin is removed by filtration, the resulting filter cake is cooled at 20°C, and the alkane solvent toluene is used for rapid washing to thoroughly remove the paraffin residue on the surface of the particles. The dioctyloxymagnesium particles treated in this step are further dispersed in a glycerol medium, and then reacted with 29.58g of silicon tetrachloride under controlled conditions. After the reaction is completed, the mixture is filtered, and then the filter cake is immersed in anhydrous ethanol and stirred to wash away the magnesium chloride generated by the reaction. After filtration, the filter cake is transferred to a toluene solvent again, and is fully stirred under heating to effectively elute the paraffin from the internal pores of the dioctyloxymagnesium particles, and finally filtered and dried to obtain pure dioctyloxymagnesium catalyst particles. In this embodiment, the molar ratio of chlorine in silicon tetrachloride to magnesium in the dioctyloxymagnesium particles is 1.969:1.

[0078] Next, at a low temperature of -20°C, 6 grams of the above-treated and dried dioctyl magnesium particles were added to 90 ml of titanium tetrachloride solution, and the temperature was gradually raised to 110°C to start the catalyst modification reaction. At this stage, 2 grams of diisobutyl phthalate were added as an internal electron donor to promote the reaction, and the reaction was maintained for 2 hours. Subsequently, the solvent in the reaction solution was filtered out, 90 ml of titanium tetrachloride was added again, the reaction temperature was maintained at 110°C, and the reaction was continued for 2 hours to fully ensure the modification of the catalyst. The total molar ratio of dioctyl magnesium to titanium tetrachloride in the above reaction was 1:77. After the reaction, the product was thoroughly washed and dried, and 2.83 grams of fine small particle size catalyst was finally obtained.

[0079] Example 6

[0080] First, 100 g of spherical diethoxy magnesium particles were evenly dispersed in 500 ml of molten paraffin and stirred at 80°C to ensure that the paraffin could fully penetrate into the pores inside the diethoxy magnesium particles. The particle size of the spherical diethoxy magnesium particles used was 10 μm and the porosity was 0.4 cm 3 / g. Subsequently, the paraffin is removed by filtration, the resulting filter cake is cooled at 30°C, and the alkane solvent n-hexane is used for rapid washing to thoroughly remove the paraffin residue on the surface of the particles. The diethoxymagnesium particles treated in this step are further dispersed in a glycerol medium, and then reacted with 72.2g of silicon tetrachloride under controlled conditions. After the reaction is completed, the mixture is filtered, and then the filter cake is immersed in anhydrous ethanol and stirred to wash away the magnesium chloride generated by the reaction. After filtration, the filter cake is transferred to a n-hexane solvent again, and is fully stirred under heating to effectively elute the paraffin from the internal pores of the diethoxymagnesium particles, and finally filtered and dried to obtain pure diethoxymagnesium catalyst particles. In this embodiment, the molar ratio of chlorine in silicon tetrachloride to magnesium in diethoxymagnesium particles is 1.946:1.

[0081] Next, under a low temperature of -20°C, 6 grams of the above-treated and dried diethoxymagnesium particles were added to 200 ml of titanium tetrachloride solution, and the temperature was gradually raised to 110°C to start the catalyst modification reaction. At this stage, 2 grams of diisobutyl phthalate were added as an internal electron donor to promote the reaction, and the reaction was maintained for 2 hours. Subsequently, the solvent in the reaction solution was filtered out, 200 ml of titanium tetrachloride was added again, the reaction temperature was maintained at 110°C, and the reaction was continued for 2 hours to fully ensure the modification of the catalyst. The total molar ratio of diethoxymagnesium to titanium tetrachloride in the above reaction was 1:70. After the reaction was completed, the product was thoroughly washed and dried, and 6.85 grams of fine small particle size catalyst was finally obtained.

[0082] Example 7

[0083] First, 100 g of spherical diethoxy magnesium particles were evenly dispersed in 500 ml of molten paraffin and stirred at 80°C to ensure that the paraffin could fully penetrate into the pores inside the diethoxy magnesium particles. The spherical diethoxy magnesium particles used had a particle size of 10 μm and a porosity of 0.2 cm 3 / g. Subsequently, the paraffin is removed by filtration, the resulting filter cake is cooled at 40°C, and the alkane solvent n-hexane is used for rapid washing to thoroughly remove the paraffin residue on the surface of the particles. The diethoxymagnesium particles treated in this step are further dispersed in a glycerol medium, and then reacted with 69.5g of silicon tetrachloride under controlled conditions. After the reaction is completed, the mixture is filtered, and then the filter cake is immersed in anhydrous ethanol and stirred to wash away the magnesium chloride generated by the reaction. After filtration, the filter cake is transferred to a n-hexane solvent again, and is fully stirred under heating to effectively elute the paraffin from the internal pores of the diethoxymagnesium particles, and finally filtered and dried to obtain pure diethoxymagnesium catalyst particles. In this embodiment, the molar ratio of chlorine in silicon tetrachloride to magnesium in diethoxymagnesium particles is 1.873:1.

[0084] Next, under a low temperature of -20°C, 6 grams of the above-treated and dried diethoxymagnesium particles were added to 200 ml of titanium tetrachloride solution, and the temperature was gradually raised to 110°C to start the catalyst modification reaction. At this stage, 2 grams of diisobutyl phthalate were added as an internal electron donor to promote the reaction, and the reaction was maintained for 2 hours. Subsequently, the solvent in the reaction solution was filtered out, 200 ml of titanium tetrachloride was added again, the reaction temperature was maintained at 110°C, and the reaction was continued for 2 hours to fully ensure the modification of the catalyst. The total molar ratio of diethoxymagnesium to titanium tetrachloride in the above reaction was 1:70. After the reaction was completed, the product was thoroughly washed and dried, and 7.04 grams of fine small particle size catalyst was finally obtained.

[0085] Comparative Example 1

[0086] The catalyst was prepared by the same method as in Example 1, except that paraffin was not used to protect diethoxymagnesium, and silicon tetrachloride was directly used to treat it, and the product was then reacted with titanium tetrachloride to prepare catalyst particles.

[0087] Measurement of particle size and sphericity

[0088] The particle sizes of the alkoxymagnesium particles used as raw materials and the prepared catalyst particles in Examples 1 to 7 and Comparative Example 1 were measured using a scanning electron microscope (SEM). The measurement results are shown in Table 1 below.

[0089] The sphericity (integrity) of the catalyst particles prepared in Examples 1 to 7 and Comparative Example 1 was observed using a scanning electron microscope (SEM). The observation results are shown in Table 1 below.

[0090] Porosity measurement

[0091] The porosity of the alkoxymagnesium particles used as raw materials in Examples 1-7 and Comparative Example 1 and the porosity of the prepared porous planarized particles (before reacting with the titanium compound) were measured by gas adsorption method. The measurement results are shown in Table 1 below.

[0092] Table 1

[0093]

[0094] From the above description, it can be further analyzed that the embodiments of the present invention not only achieve an effective reduction in the particle size of the polyolefin catalyst, but also maintain the sphericity and pore structure of the catalyst particles, which is crucial to improving the performance of the catalyst. Specifically, the particle size of the catalyst in Example 2 is reduced to a minimum of 1 μm, which indicates that the method of the present invention has made a significant breakthrough in particle size control and provides a more ideal catalyst selection for the 3D printing application of polyolefin powder.

[0095] By observing the catalyst particles using a scanning electron microscope (SEM), it can be clearly seen that the catalyst particles prepared in Examples 1 to 7 all maintain good sphericity. This shows that the chemical etching method of the present invention can effectively avoid the destruction of the morphology of the catalyst particles when processing the alkoxy magnesium particles, thereby maintaining the fluidity of the catalyst, which is particularly important for the uniform distribution of the powder material in the SLS technology and the smooth progress of the sintering process.

[0096] On the other hand, through the observation of comparative example 1, we found that the catalyst particles could not maintain the original sphericity after being treated with chlorinated silane compounds. This was mainly because liquid paraffin was not used for pore protection during the reaction, resulting in excessive intrusion of chlorinated silane compounds and destruction of the pore structure of the particles. The destruction of the pore structure not only affects the activity of the catalyst, but also causes changes in the morphology of the particles, making it possible for the catalyst to fail to provide a stable polymerization environment in the subsequent polymerization process.

[0097] It is worth noting that the present invention maintains the porosity of the porous flattened particles of Examples 1 to 7 similar to that of the original alkoxymagnesium particles through the protective effect of liquid paraffin during the preparation process, which means that the catalyst retains its porosity and high surface area while maintaining a small particle size, which is of great significance for improving catalyst activity and controlling the particle size distribution of polyolefin powder. The porosity of the flattened particles in Comparative Example 1 is significantly increased, which may be due to the excessive filling of the pores by the chlorinated silane compound, resulting in an adverse change in porosity, thereby affecting the performance and application effect of the catalyst.

[0098] In summary, the present invention provides a chemical etching method that can effectively control the catalyst particle size, maintain the catalyst sphericity and pore structure. Compared with the prior art, the method of the present invention shows significant advantages in optimizing catalyst performance and opens up new possibilities for the application of polyolefin powder in the field of 3D printing.

[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a catalyst, characterized in that: The following steps are involved: S1, immersing the alkoxy magnesium particles in melted paraffin wax, heating the mixture to a temperature in the range of 70 to 120° C., and stirring the mixture sufficiently so that the pores of the particles are filled with the paraffin wax; S2, filtering the mixture of the paraffin wax and the particles, cooling the filter cake to a temperature in the range of 0 to 40° C., and removing the paraffin wax on the surface of the particles; S3, using a chlorinated silane compound to smooth the surface of the particles to generate a product mixture; S4, filtering and washing the product mixture to obtain flattened particles; S5, removing the paraffin in the pores of the planarized particles to obtain porous planarized particles; as well as S6, adding the porous planarized particles to a titanium compound at a temperature of -20 to 110°C to react and obtain a catalyst.

2. The method according to claim 1, characterized in that The molar ratio of total chlorine atoms in the chlorinated silane compound to total magnesium atoms in the alkoxymagnesium particles is in the range of 1.751:1 to 1.985:

1.

3. The method according to claim 1, characterized in that The alkoxy magnesium particles include dimethoxy magnesium, diethoxy magnesium, dipropoxy magnesium, dibutoxy magnesium, dioctyloxy magnesium or any combination thereof.

4. The method according to claim 1, characterized in that: The particle size of the magnesium alkoxide particles is in the range of 5 μm to 10 μm.

5. The method according to claim 1, characterized in that The porosity of the alkoxy magnesium particles is 0.1 cm 3 / g to 1cm 3 / g range.

6. The method according to claim 1, characterized in that Step S2 further includes removing the paraffin on the surface of the particles using a first solvent, wherein the first solvent is an alkane solvent.

7. The method according to claim 6, characterized in that The first solvent is selected from n-hexane, cyclohexane, n-octane, isooctane, xylene, toluene, ethane, propane and any combination thereof.

8. The method according to claim 1, characterized in that Step S3 further includes dispersing the mixture in a second solvent, adding the chlorinated silane compound, so that the chlorinated silane compound reacts with the alkoxymagnesium on the surface of the particles, wherein the second solvent is a poor solvent for paraffin.

9. The method according to claim 8, characterized in that The second solvent is selected from water, methanol, ethanol, glycerol and any combination thereof.

10. The method according to claim 1, characterized in that The chlorinated silane compound is selected from SiC14, Si(OCH3)Cl3, Si(OCH3)2Cl2, Si(OC2H5)Cl3, Si(OC2H5)2Cl2, Si(OC2H5)3Cl, Si(OC4H9)Cl3, Si(OC4H9)2Cl2, Si(OC4H9)3Cl and any combination thereof.

11. The method according to claim 1, characterized in that: The titanium compound is selected from TiC14, TiC13, Ti(OCH3)Cl3, Ti(OCH3)2Cl2, Ti(OCH3)3Cl, Ti(OC2H5)Cl3, Ti(OC2H5)2Cl2, Ti(OC2H5)3Cl, Ti(OC4H9)Cl3, Ti(OC4H9)2Cl2, Ti(OC4H9)3Cl and any combination thereof.

12. The method according to claim 1, characterized in that A molar ratio of the porous planarizing particles to the titanium compound is in the range of 1:20 to 1:

100.

13. A catalyst prepared according to the method of any one of claims 1 to 12.

Citation Information

Cited By

  • Solid catalyst component, catalyst, process for the preparation and process for the polymerization of olefins

    CN123003768A

  • A catalyst component, a process for the preparation thereof and a catalyst

    CN123003770A